Changing the orientation of youths towards street hawking in Ibadan, Nigeria. - Ahmed olaitan adebisi (University of Turin, 2021)
Vast majority of youths in developing economy are unemployed and street hawking is a succor to a great number of them for survival. Despite the vital role of street hawking in the livelihoods of youths in a recessed economy, its adverse implications on urban space and social well-being of the youths are too critical to overlook. This study, therefore, examines the implication of street hawking and causal factors motivating street hawking among youths in Sango-Ojoo axis of Ibadan. The study was a descriptive survey among 37 youths who were randomly sampled at potential hawking terminals along Sango-Ojoo road. Data was collected through the use of multiple choice questionnaires, and interview guide, while chi-square test was used in the data analysis. Findings revealed a preponderance of female youth hawkers who had attained secondary education. The causative factors motivating youths to hawk include; low level of education, household size, occupation of hawkers’ employers and income. The study further established a statistical significance between street hawking and vulnerability of the youths in human environments. The paper recommends sustainable policy through quality and affordable education to the poor, empowerment programme and habitual campaign on the dangers of street hawking to stem the scourge of hawking in Ibadan.